PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY, EARNING PER SHARE, UMUR PERUSAHAAN, UKURAN PERUSAHAAN, DAN REPUTASI AUDITOR TERHADAP UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA TAHUN 2018 - Iska, Pratiwi Ajeng; Hariadi, Hariadi; Azwir, Nasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The aim of this study is to examine the influence of Debt To Equity Ratio, Return On Equity, Earning Per Share, Firm’s Age, Firm’s Size, and Auditor Reputation toward Underpricing on companies conducted Initial Public Offering (IPO) in Indonesia Stock Exchange in 2018. The population of this study is the companies conducted Initial Public Offering (IPO) which are listed in Indonesia Stock Exchange in 2018. The number of sample used in this research are 57 companies with purposive sampling method. Data are analyzed using multiple regression analysis method at level significance 5% using SPSS (Statictical Product and Service Solution) version 20. The results showed that Firm’s Age and Auditor Reputation have significant effect toward Underpricing at the level of 5%. While Debt To Equity Ratio, Return On Equity, Earning Per Share, and Firm’s Size have no effect on UnderpricingKeywords : Debt To Equity Ratio, Return On Equity, Earning Per Share, Firm’s Age, Firm’s Size, Auditor Reputation, Underpricing